THU0515 Disability and lower quality of life is associated with socioeconomic passivity in young adults with juvenile idiopathic arthritis. (15th June 2017) - Rebane, K; Ristolainen, L; Relas, H; Orenius, T; Kautiainen, H; Luosujärvi, R; Aalto, K; Säilä, H
Abstract : Background: Health related quality of life of adult patients with juvenile idiopathic arthritis (JIA) is shown to be significantly lower compared to the general population. 1, 2 Objectives: We aimed to recognize young adults with JIA who are socioeconomically passivated and to assess which areas of self-rated health are associated with the emergence of passivity symptoms. Methods: We studied 195 young adults with JIA using questionnaires addressing demographics, health behavior, and physical activity. The HAQ questionnaire was used to assess functional ability, quality of life was assessed with RAND-36, depressive symptoms were assessed with BDI-II, and self-esteem was evaluated by using the Rosenberg scale. Patients were classified as active if they were engaged in studying, working, maternal leave or military service; and as passive, if they were unemployed or on disability pension. Results: 80% of the patients were female, mean age was 23 years, and disease duration was approximately 15 years. Patients in the passive group participated less in leisure time non-physical activities ( p =0.033), they felt more disturbed during their leisure time ( p =0.010). Leisure time physical activity did not reveal statistically significant differences between the groups. The majority of the patients in the passive group (58%) had only basic education ( p <0.001), they visited their doctor more frequently ( p =0.019) and they used oral prednisolone more often ( p <0.018). Approximately 70% of the patients received disease modifying antirheumatic drugs, and nearly half of the patients were treated with biologicals in both of the groups. Mean disability scores on HAQ were higher in the passive group ( p =0.012). Depressive symptoms did not differ between the groups. Self-esteem was lower in the passive group ( p =0.002). Results in health related quality of life revealed statistically significant differences between the groups: physical functioning ( p =0.049), social functioning ( p =0.020), and emotional well-being ( p =0.047) were significantly lower in the passive group. Conclusions: Patients being socioeconomically more passive showed higher degrees of disability, reporting lower physical functioning, self-esteem, emotional well-being, and social functioning. Those patients should be recognized earlier and activating interventions should be provided. References: Foster HE, Marshall N, Myers A, Dunkley P, Griffiths ID. Outcome in adults with juvenile idiopathic arthritis: A quality of life study. Arthritis Rheum. 2003;48(3):767–75. Barth S, Haas JP, Schlichtiger J, Molz J, Bisdorff B, Michels H, et al. Long-Term Health-Related Quality of Life in German Patients with Juvenile Idiopathic Arthritis in Comparison to German General Population. PLoS One. 2016;11(4): e0153267. Disclosure of Interest: None declared